OMG! all about me diary - Russell, Rachel R.; Russell,Nikki (Simon and Schuster UK Ltd.: London, 2013)
Fill in the blanks of the Dork Diary write-in journal, filled with questions for every day and complete with art and quotes from Nikki Maxwell herself! As Nikki Maxwell knows, keeping a journal is a great way to get to know the most important person in your life: YOU! This special Dork Diaries guided journal features questions for every day of the year. If you could swap places with anyone for a day, who would it be and why? What song could you listen to 100 times? What TV show are you totally obsessed with right now and why? What's the fiercest outfit in your closet?
Keywords: English, Fiction